Developing a Peer Tutoring–Based Social Scaffolding Model in Project-Based Learning to Enhance University Students’ Academic Writing Skills - Kusmanto, Hari; Purnomo, Eko; Santoso, Tri; Kamaluddin Mabruri, Zuniar; Gita Putri, Anisa; Setiyoningtiyas, Desy (Jurnal VARIDIKA, 2026)
Increased focus on academic writing within higher education has not been matched by appropriate models of instruction that can bring about the collaborative learning and social scaffolding necessary for optimal student writing performance. The objectives of this study are (1) to analyse students’ needs and characteristics, (2) to develop a Project Based Learning of peer tutoring model as integrated social scaffolding in the academic writing instruction, and (3) to see the validity, practicality, and effectivity of the developed model. This study used a Research and Development (R&D) strategy in the 4D model (define, design, develop, and disseminate). One hundred twenty undergraduates participated in the study, which was conducted at Universitas Muhammadiyah Surakarta and UINSurakata in their academic writing courses. MethodsThe study used mixed methods to analyze data collected from needs analysis surveys, expert validation sheets, student response questionnaires, pre- and post-tests, interviews, and documentation. Results show that developed model has a high rate of validity (CVI = 0.94) & high rate of practicality (89.1%). Additionally, students improved significantly in their academic writing abilities from pretest (M = 54.62) to posttest (M = 76.14) over the course of several weeks, creating a gain of 21.52 (p <. 001; Cohen’s d = 1.98). This study shows that the improvement of students in academic writing was shown from the process and product quality with peer tutoring as social scaffolding implemented in PjBL model.